Performance of Brushless DC Drive with Single Current Sensor Fed from PV with High Voltage-Gain DC-DC Converter - G. G RajaSekhar; Basavaraja Banakara (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents the performance of Brushless DC (BLDC) Motor drive with only one positioning sensor instead of three conventional sensors. The three sensor units are replaced with a single stator current sensor unit in DC bus which further reduces the cost increasing the reliability of the drive system. Using a single sensor in stator requires minimum electronic equipment for the purpose of measurement process. This paper evolves the BLDC motor drive fed from PV system. A high voltage-gain DC-DC converter is presented in this paper to step-up the voltage from PV system. The appropriateness of PV fed BLDC motor drive is verified for variable increamental speed with fixed torque and variable decremental speed with fixed torque operating conditions. BLDC motor drive performance is also performed for variable torque with fixed peed working condition. The proposed system and results are developed using MATLAB/SIMULINK software.